Paciente masculino de 38 años de edad con cirrosis hepática descompensada. - Prado López, Rody Joao (2020)
The present clinical case deals with a 38 year old male patient with decompensated cirrhosis of the liver who attended the medical consultation due to fatigue, dizziness, jaundice, difficulty walking, drowsiness, edema in the lower limbs and abdominal distention. He indicates not having a personal pathological history and is also an alcoholic, smoker 10 cigarettes a day. A nutritional intervention is carried out with the aim of avoiding the progression of complications in the patient with decompensated liver cirrhosis through the nutritional care process. In the anthropometric evaluation we have a weight of 60kg and a height of 169 cm, abdominal circumference 116 cm which reflects a normal nutritional status according to the WHO with a BMI of 18.94 kg / m2. Regarding the biochemical evaluation, an alteration of the lipid profile is evidenced with high values, serum proteins within the limit, elevated liver enzymes, hyperbilirubinemia, hyperammonemia, all these altered data are the product of decompensation of liver cirrhosis. A 2300 kcal diet is prescribed, hypoprotein for 48 h, divided into 5 meal times, moderate volume, warm temperature and a contribution of 25g fiber. The progression of complications was prevented through the nutritional care process. A control of the dietary plan is maintained, according to the follow-up it was observed that, through the assessment, diagnosis and nutritional intervention, the patient presents favorable changes in terms of his pathological condition and nutritional status.